MODERATING IMPACT OF BOARD SIZE ON RISK MANAGEMENT COMMITTEE CHARACTERISTICS AND EARNINGS QUALITY OF LISTED OIL AND GAS COMPANIES IN NIGERIA - Abba, Hirhyel Ibrahim; Shehu, Usman Hassan; Bala, Hussaini (Kashere Journal of Management Sciences, 2024)
The cases of earning manipulation are still prevalent among industries in Nigeria despite the implementation of several corporate governance mechanisms. This study investigates the moderating impact of board size on the relationship between risk management committee characteristics and earnings quality of listed oil and gas companies in Nigeria. The study uses ex- post facto research design. Earning quality is proxied by discretionary accruals while risk management committee is characterised by risk management committee size, risk management committee diligence and risk management committee independence. The study used secondary data which was extracted from the annual report and accounts of the listed oil and gas companies for a period for 7 years, from 2015 to 2021.Panel corrected standard error approach of estimation was employed in analysing the data. Findings from the study reveal that board size has significant moderating effect on risk management committee size, risk management committee diligence and risk management committee independence on earnings quality of listed oil and gas companies in Nigeria. As such, the study recommends that, oil and gas companies should maintain optimal board size as it has the capability to moderate the impact of risk management committee on earnings quality.